2020
DOI: 10.3390/brainsci10080541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Convulsive Properties of Aqueous Kava Extract on Zebrafish Using the PTZ-Induced Seizure Model

Abstract: Kava roots have been extensively studied in clinical trials as potential candidate anti-anxiety drugs. However, anti-convulsive properties of various tissues of stems of Kava have not been reported to date. The objective of the study was to evaluate the anti-convulsive potential of aqueous extracts prepared from specific tissues of Kava (Piper methysticum) stems in zebrafish, using the PTZ-induced seizure model. The potency of each extract was compared in terms of the intensity of seizure scores and onset time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Few studies evaluated bdnf expression, that is involved in neuroplasticity, in adults, and the majority used 170 mg/kg ip. injection to induce seizures and some did not find any alteration (Choo et al, 2018(Choo et al, , 2019Jaiswal et al, 2020), while some observed a decrease in this gene expression [88,133]. Little is known about oxidative stress in adult zebrafish exposed to PTZ.…”
Section: Pentylenetetrazole (Ptz)mentioning
confidence: 99%
“…Few studies evaluated bdnf expression, that is involved in neuroplasticity, in adults, and the majority used 170 mg/kg ip. injection to induce seizures and some did not find any alteration (Choo et al, 2018(Choo et al, , 2019Jaiswal et al, 2020), while some observed a decrease in this gene expression [88,133]. Little is known about oxidative stress in adult zebrafish exposed to PTZ.…”
Section: Pentylenetetrazole (Ptz)mentioning
confidence: 99%
“…Another in vivo study evaluated the anticonvulsant effects of kavas' stem peelings in the zebrafish model. An aqueous extract of kava without peel after 45 min of pre-treatment showed an anticonvulsant potential at a dose of 50 mg/L [92]. Another clinical trial develops a kava-based intervention to enable tobacco cessation and reduce lung cancer risk in active smokers who have no intention to quit smoking (www.clinicaltrials.gov, accessed on 22 February 2022).…”
Section: Clinical Potential Uses Of Kava In Non-cancer Diseasesmentioning
confidence: 99%